Exploring the Implementation of Quipper School Platform in English Teaching - Andi Ratu Nurhazana; Nurdin Noni; Sukardi Weda (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The objectives of this research were to find out the implementation of Quipper School platform in English teaching as used by the teacher, to find out the students’ perception toward the implementation of Quipper School platform, and find out inhibiting and supporting factors in implementing Quipper School in English teaching. The researcher used mixed method. This research was conducted at SMA Negeri 2 Makassar. The subject of the research consisted of one English teacher and 25 students from class XII IPA 3. The data were obtained through observation checklist, interview, and questionnaire. The result of this research revealed that the teacher implemented five stages in the implementation of Quipper School as platform in English Teaching. Then, the students’ perception of the implementation of the Quipper School platform in teaching English used two instruments i.e., interview and questionnaire. Based on the students’ interview, most gave positive perception toward the platform used by the teacher in teaching and learning. The students’ perception regarding Quipper School was very good to use. The students feel very interested in learning English. Quipper School can increase the students’ learning motivation. Then, Quipper School platform makes it easier for students to understand learning and adds insight. Meanwhile, the questionnaire shows that the students’ perception of interest and motivation were neutral, and the students’ perceptions of the facilitating condition was neutral. The last, the inhibiting factors in implementing Quipper School platform are network problem, and internet quota. The supporting factors in implementing Quipper School platform as used by the teacher in class are the material and system quality.Keywords: Implementation, Perception, Quipper School Platform, English Teaching